2004
DOI: 10.1016/s0002-9440(10)63246-4
|View full text |Cite
|
Sign up to set email alerts
|

CTNNB1 Mutations and Overexpression of Wnt/β-Catenin Target Genes in WT1-Mutant Wilms' Tumors

Abstract: Gain-of-function mutations in exon 3 of beta-catenin (CTNNB1) are specific for Wilms' tumors that have lost WT1, but 50% of WT1-mutant cases lack such "hot spot" mutations. To ask whether stabilization of beta-catenin might be essential after WT1 loss, and to identify downstream target genes, we compared expression profiles in WT1-mutant versus WT1 wild-type Wilms' tumors. Supervised and nonsupervised hierarchical clustering of the expression data separated these two classes of Wilms' tumor. The WT1-mutant tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
133
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 26 publications
(25 reference statements)
12
133
0
Order By: Relevance
“…Furthermore, WTX mutations are not associated with differences in the clinical presentation or outcome of Wilms tumors (Wegert et al, 2009). Microarray experiments show distinct differences in the gene expression profile of WT1 wild-type and mutant tumors, with many of the changes in the WT1 mutant tumors due, in part, to activation of the Wnt pathway (Li et al, 2004). Gene expression profiles of WT1-replete, CTNNB1 wild-type Wilms tumors with or without WTX mutations, may clarify the role of WTX in Wilms tumorigenesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, WTX mutations are not associated with differences in the clinical presentation or outcome of Wilms tumors (Wegert et al, 2009). Microarray experiments show distinct differences in the gene expression profile of WT1 wild-type and mutant tumors, with many of the changes in the WT1 mutant tumors due, in part, to activation of the Wnt pathway (Li et al, 2004). Gene expression profiles of WT1-replete, CTNNB1 wild-type Wilms tumors with or without WTX mutations, may clarify the role of WTX in Wilms tumorigenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Sporadic Wilms tumors may be associated with bi-allelic mutation of WT1 in up to 15% of cases (reviewed in (Huff, 1998)). Loss of WT1 is frequently accompanied by gain of function mutations of CTNNB1 (Koesters et al, 1999;Maiti et al, 2000;Li et al, 2004). Sporadic Wilms tumors without WT1 mutation frequently show loss of imprinting of IGF2 locus and many genes within this region may be deregulated (Ogawa et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…WT1 mutations are strongly associated with ILNR (Beckwith, 1998) that often develop into WTs with ectopic mesenchymal elements (Beckwith et al, 1990;Beckwith, 1998). A series of immunohistochemical studies of b-catenin in WT have shown that nuclear accumulation of b-catenin is predominantly observed in mesenchymal cells irrespective of CTNNB1 mutations (Koesters et al, 2003;Li et al, 2004;Fukuzawa et al, 2004aFukuzawa et al, , 2008Zirn et al, 2006). These observations suggest a relationship between the mesenchymal lineage in WT and active WNT signalling.…”
Section: Introductionmentioning
confidence: 99%
“…The WNT-signalling pathway is known to be involved in a subset of WT (Koesters et al, 1999(Koesters et al, , 2003Maiti et al, 2000;Li et al 2004;Fukuzawa et al, 2004a). These tumours typically have WT1 mutations and/or CTNNB1 mutations (Koesters et al, 1999;Maiti et al, 2000;Li et al, 2004;Fukuzawa et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation